Addressing of existing problems of intellectual property valuation in Vietnamese system of laws - Phuong, Hoang Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The intellectual property (IP) valuation was conducted in Vietnam long years ago before the promulgation of the Intellectual Property Law (IP Law) in 2005. Nevertheless this activity does not follow any standards due to the actual situation of legal documents in this field which, in many cases, remain simple and overlapping. The actual legal documents of Vietnam for IP valuation do not govern directly the pricing aspects of IP assets themselves but only give conceptual regulations of computational procedures (based on book values) of intangible assets including IP ones. Even in legal documents specifically applied for IP field, such as IP Law and related Circulars, there are no regulations applied for IP valuation. The set-up of an integrated system of IP valuation in a close future definitely requires a unified system of legal documents to cover actually existing shortcomings in this field.